Transformasi Ungkapan Tradisional dalam Perkawinan Adat Makassar di Era Modern - Indramini Indramini (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2024)
This research aims to examine the transformation of traditional expressions in the Makassar traditional wedding procession in the modern era. The main focus of the research is to understand how these expressions adapt to social change, technology and modern values, as well as their impact on preserving the culture and identity of the Makassar community. The method used in this research is a qualitative approach with in-depth interview techniques and participant observation. The research results show that although some traditional expressions have undergone modifications to adapt to the modern context, the core of the cultural values ​​contained are still maintained. This transformation reflects adaptive cultural dynamics and shows that modernization does not always threaten tradition, but can serve as a means of strengthening and enriching cultural heritage. This research emphasizes the importance of striking a balance between preserving traditions and innovating so that these traditions remain relevant amidst changing times.